Aerosol loading over the South African Highveld - Bigala, Thomas Aquinas (My University, 2009)
The Highveld region of South Africa contributes substantially to the aerosol loading over southern Africa because of its importance as an industrial, mining and farming base. Aerosols affect climate by absorbing or reflecting incoming solar radiation, and by affecting cloud microphysics, cloud albedo and precipitation. The physical and optical properties of industrial/urban aerosols over the Highveld region of South Africa were analysed during a 32-day winter sampling period (21 May to 21 June) in 2002; a 32-day summer sampling period (21 October to 21 November) in 2002, and a second 32-day winter sampling period (19 May to 19 June) in 2003. Synoptic circulation systems were examined in as far as they affect the horizontal transport of aerosols over the Highveld region. Measurements of aerosol optical thickness (AOT) from the ground to the top of the atmosphere and aerosol size distribution characteristics over the Highveld region were taken using hand-held hazemeters and a CIMEL sun photometer. The AOT observed over the region during the winter 2002 and 2003 sampling periods and during the summer 2002 sampling period indicated high turbidity. In the 2002 winter sampling period, the AOT530nm ranged between 0.05 to 0.7 with an average of 0.14. In the 2002 summer sampling period, the AOT530nm ranged between 0.05 to 0.6, with an average of 0.24. In the 2003 winter sampling period, the AOT500nm ranged between 0.06 to 0.6, with an average of 0.21. The Ångström exponent value had a wide range, 0.8 to 2.4 in the 2002 winter and summer sampling periods and also in the 2003 winter sampling period, indicating that a range of particle sizes was present over the Highveld region. The Ångström exponent values obtained were derived from the influences of Aeolian dust, coarse-mode industrial particles and, to a small extent, fine-mode biomassburning aerosols. Case studies, based on trajectory analysis and meteorology of the sampling area, were made of the aerosols emanating from the township sites during each of the three sampling periods to observe the build-up and dispersion of aerosols at that time.
Keywords: Aerosol loading; hand-held hazemeter; CIMEL sun photometer; Angstrom exponent values; aerosol optical thickness values